PEEK Cages versus Titanium-Coated PEEK Cages in Single-Level Anterior Cervical Fusion: A Randomized Controlled Study - Schröder, Johannes; Kampulz, Thomas; Bajaj, Sonunandita K.; Hellwig, Arnd Georg; Winking, Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The implantation of a spacer is a common practice after anterior diskectomy in cervical spine. Polyether ether ketone (PEEK) cages have replaced titanium implants due to their better radiologic visibility and appearance in postoperative magnetic resonance imaging (MRI) scans. However, PEEK showed apparently higher nonunion rates than titanium cages. The aim of the study was to evaluate the fusion behavior of plain PEEK cages in comparison to titanium-coated PEEK (TiPEEK) cages.Method We randomized 104 patients with single-level cervical radiculopathy or mild myelopathy. They were divided into two groups of 52 patients each, receiving either a PEEK cage or the titanium-coated variant of the same cage type. The 1- and 2-year follow-ups were completed by 43 patients in the PEEK group and by 50 patients in the TiPEEK group. Fusion was determined by plain X-ray and lateral functional X-ray.Results Two years after surgery, a complete fusion was observed in 37 patients of the PEEK group (86%). Six cases were considered as nonunions. In the TiPEEK group, we found 41 fusions (82%) and 9 nonunions at this time. The difference was not considered significant (p = 0.59). The clinical evaluation of the two groups showed no difference in the neurologic examination as well in the pain scores over the time period.Conclusions Despite some assumptions about an advantage of TiPEEK over PEEK cages for fusion in cervical spine surgery, this prospective randomized controlled study did not find an accelerated or improved fusion using TiPEEK for anterior cervical diskectomy.
Keywords: cervical disk herniation; cervical radiculopathy; cervical cages; cervical fusion